50 Years of the Radiation Exposure Information and Reporting System. (3rd April 2022) - Hagemeyer, Derek; Nichols, Gregory; Mumma, Michael T.; Boice, John D.; Brock, Terry A.
Abstract: Purpose: As the Radiation Exposure Information and Reporting System (REIRS) celebrates 50 years of existence, this is an appropriate time to reflect on the innovative and novel system and how it has shaped the study of occupational radiation exposure. It is also fitting to appreciate the vision and initiative of the individuals who recognized the future value of the collection and analysis of this information to better inform regulations, policies, and epidemiologic studies, and thus contribute to the protection of workers and the public from the adverse health effects of radiation exposure. Conclusions: REIRS has evolved and expanded over its 50-year history and has played a central role in providing the radiation exposure monitoring records for the Million Person Study for individuals monitored as NRC licensees and at DOE facilities. REIRS has played two major functions in epidemiologic studies. First, it has provided dosimetry information on individual workers in occupational studies to ensure nearly complete ascertainment of career doses. Second, REIRS was used as the primary data source for large cohorts within the Million Person Study: nuclear power plant workers ( n ∼140, 000) and industrial radiographers ( n ∼130, 000). The legacy that REIRS continues to uphold is a model for creating and maintaining a successful tool throughout decades of political, technological, and demographic change.